PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN METODE FONIK BERBANTUAN MEDIA PUZZLE DI SEKOLAH DASAR - Meynita Pratasya; Iis Aprinawati; Fadhilaturrahmi; Putri Hana Pebriana; Yenni Fitra Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ early reading skills through the phonics method assisted by puzzle media in Grade I students of UPT SDN 009 Simpang Kubu in the 2024/2025 academic year. The type of research used in this study is Classroom Action Research (CAR). The subjects of this study were the students, while the objects of the study were the phonics method assisted by puzzle media and students’ early reading skills. The research was conducted in two cycles, with each cycle consisting of two meetings. The data collection techniques used in this study were observation, tests, and documentation. The results showed an increase in the number of students who achieved the Learning Objective Achievement Criteria (KKTP), as well as an improvement in the class average score and classical mastery. The percentage of classical mastery in Cycle I Meeting I was 61.90%, increased to 76.19% in Cycle I Meeting II, then increased significantly to 90.47% in Cycle II Meeting I, and reached 95.23% in Cycle II Meeting II. Based on the results of the study, it can be concluded that the phonics method assisted by puzzle media can effectively improve the early reading skills of Grade I students at UPT SDN 009 Simpang Kubu.